Nutrition and feeding of organic poultry - Blair, Robert, 1933- (CABI, 2018)
"Organic poultry production has increased significantly in recent years to keep up with increasing consumer demand for organic eggs and meat. There are many guidelines and restrictions on what should go into the feed of organically-farmed poultry, from which difficulties arise when trying to ensure a well-balanced nutritious diet without the use of any unapproved supplements. This, the second edition of Robert Blair's classic and bestselling book on the nutrition and feeding of organic poultry, presents advice for organic producers, and the agencies and organizations serving them"--Publisher's description